Ulam Stability of a Quartic Functional Equation. (29th April 2012) - Bodaghi, Abasalt; Alias, Idham Arif; Ghahramani, Mohammad Hosein
Abstract : The oldest quartic functional equation was introduced by J. M. Rassias in (1999), and then was employed by other authors. The functional equation f ( 2 x + y ) + f ( 2 x - y ) = 4 f ( x + y ) + 4 f ( x - y ) + 24 f ( x ) - 6 f ( y ) is called a quartic functional equation, all of its solution is said to be a quartic function . In the current paper, the Hyers-Ulam stability and the superstability for quartic functional equations are established by using the fixed-point alternative theorem.